Contributing factors and associated risks in case of decision-making by a nurse during the inter-hospital transport of a patient affected by COVID-19 (Research, Society and Development, 2021)
The complexity involved in inter-hospital care imposes a series of ethical issues on nurses, which are related to customer care, the work environment and organizational processes. Additionally, the current state of health emergency, characterized by the COVID-19 pandemic, determines reorganizations in the work process and an increase in the emotional tension of professionals. The aim of this study was to analyze the contributing factors and associated risks in the case of decision-making by a nurse during inter-hospital transport of a patient affected by COVID-19, published in the Brazilian media. Descriptive, theoretical and reflective study, supported on videos and journalistic articles, based on the cause and effect diagram (Ishikawa diagram) and on the risk assessment matrix, developed between February and March 2021. The causes of the decision-making of the professional in the face of a critical situation in inter-hospital care were identified., the main one being the interdiction of the road. The analysis of the risks to which the nurse and the patient were exposed allowed reflection on the importance of adequate support for professionals during inter-hospital care and a detailed planning for this situation, in order to minimize them and ensure safety for everyone involved.